Implementation of madrasah self-evaluation and electronic-based madrasah work and budget plan at Madrasah Aliyah Fathurrahman Batu Sopang - Ramadhina, Marini Shadrina; Hifni, Hifni; Suratman, Suratman (CAHAYA PENDIDIKAN, 2024)
This study examines the implementation of Madrasah Self-Evaluation (EDM) and the Electronic-Based Madrasah Work and Budget Plan (e-RKAM) at Madrasah Aliyah Fathurrahman in Batu Sopang, Paser Regency. EDM functions as a tool for assessing institutional performance according to the 8 National Education Standards (SNP), helping identify strengths and areas for improvement. Meanwhile, e-RKAM facilitates more transparent and accountable budget planning, aligning financial resource allocation more closely with institutional needs. Research on EDM and e-RKAM implementation is essential to enhancing educational quality, budget transparency, digital skills, and data-driven planning, as well as providing practical recommendations and insights for madrasah educational policy.This study employs a qualitative descriptive approach, collecting data through interviews, observations, and documentation. Data analysis was conducted using data triangulation techniques, comparing findings from interviews, observations, and documents to ensure consistency and accuracy of information. Results indicate that EDM and e-RKAM have improved budget preparation efficiency and financial management at the madrasah. The use of EDM enables more systematic, data-based decision-making, while e-RKAM enhances transparency in budget allocation and expenditure monitoring. However, challenges such as limited digital literacy and infrastructure gaps remain. This highlights the need for ongoing training and resource development to maximize EDM and e-RKAM’s potential. Nonetheless, the integration of these tools positively impacts educational quality and governance within the madrasah.